Manifestation of Dark and Social Humor in the use of the Irony Rhetorical Industry in Nahj al-Balaghah [In Persian] - Mohammad Etrat Doost (International E-Research Foundation (Bonyan Pouya Pajooh Andisheh Institute), 2021)
The words of Imam Ali (AS) in Nahj al-Balaghah have always been distinguished from other texts due to two basic characteristics: One is eloquence and rhetoric, and the other is its multidimensionality, that is the words of Imam Ali have appeared in different and possibly contradictory semantic fields, and at the same time it has maintained its eloquence and rhetoric. An example of the intersection of these two characteristics can be seen in the use of the ironic rhetoric industry, which some have equated with dark and social humor. What is most noticeable in this array is the juxtaposition of two contrasting semantic-verbal elements to surprise the audience and at the same time convey a dark message with humorous literature. In this article, by identifying examples of the manifestation of the Irony rhetorical industry in the sermons of Nahj al-Balaghah and their conceptual analysis, another manifestation of the verbal and semantic miracle of Imam Ali (as) as Amir of words is considered and another literary industry used in Nahj al-Balaghah to be read and studied. The findings of the study show that irony is used more in secret, combining contradictory and unexpected topics, exaggerating in preferring worthless topics and vice versa and with striking sentences and divination in the words of Imam Ali (AS) so that many important concepts are conveyed to the audience through humorous literature in this way.